Fate of Microplastic Pollution Along the Water and Sludge Lines in Municipal Wastewater Treatment Plants - Thibaut Saur; Florian Paillet; Samuel Robert; Jean-Claude Alibar; Jean-François Loret; Bruno Barillon (Microplastics)
Microplastics have emerged as a global environmental concern due to their widespread presence and potential effects on ecosystems. Wastewater treatment plants (WWTPs) play a critical role in mitigating the release of microplastics into the environment. This study aimed to evaluate the abundance and distribution of microplastics in three municipal WWTPs exhibiting different sludge and water treatment technologies. Samples were collected at various stages of the treatment process, including influent, primary and biological sludge, treated water, thickened sludge and dehydrated sludge. Quantification analyses were performed and then coupled with operational data to assess pollution flow rates and the microplastic balance. An important removal rate (>97%) of microplastics along the water line was observed in all three WWTPs. The lower performance of 0.75 mm screening was observed regarding microplastic capture compared to conventional primary settling on the water line. No significant differences in the pollution flow rates between primary and biological sludge were detected. Whatever the thickening and dehydration technologies that were tested, the specific quantities of microplastics along the sludge treatment lines were steady, implying the comparable behaviour of microparticular pollution to total suspended solids. These results underscored the important role of the different concentration stages of sludge treatment lines in sequestrating microplastics within the sludge fraction.